2016
DOI: 10.1002/adhm.201500617
|View full text |Cite
|
Sign up to set email alerts
|

Bedside, Benchtop, and Bioengineering: Physicochemical Imaging Techniques in Biomineralization

Abstract: The need to quantify physicochemical properties of mineralization spans many fields. Clinicians, mineralization researchers, and bone tissue bioengineers need to be able to measure the distribution, quantity, and the mechanical and chemical properties of mineralization within a wide variety of substrates from injured muscle to electrospun polymer scaffolds and everything in between. The techniques available to measure these properties are highly diverse in terms of their complexity and utility. Therefore it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 166 publications
0
5
0
Order By: Relevance
“…Even when cells contact mineral, are they passive bystanders or are they taking an active role in the calcification process? We define two theoretical extremes along this spectrum: unregulated mineralization (only rules of physics apply, and we can expect processes similar to abiotic mineralization) and regulated mineralization (cells actively coordinate mineralization, similar to physiological mineralization of bone, but the bone is forming at the wrong place, e.g., heterotopic ossification [ 22 ] ). In between, we propose the term “dysregulated mineralization,” which comprises a continuum of processes in which the role cells play in mineral formation ranges from apparently passive to overtly active.…”
Section: Pathological Calcificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Even when cells contact mineral, are they passive bystanders or are they taking an active role in the calcification process? We define two theoretical extremes along this spectrum: unregulated mineralization (only rules of physics apply, and we can expect processes similar to abiotic mineralization) and regulated mineralization (cells actively coordinate mineralization, similar to physiological mineralization of bone, but the bone is forming at the wrong place, e.g., heterotopic ossification [ 22 ] ). In between, we propose the term “dysregulated mineralization,” which comprises a continuum of processes in which the role cells play in mineral formation ranges from apparently passive to overtly active.…”
Section: Pathological Calcificationmentioning
confidence: 99%
“…Such processes produce a bone‐like material in a pathological context, e.g., heterotopic bone formation, also called osseous metaplasia. [ 22 ] Regulated pathological mineralization requires a change in the cell type, through differentiation or phenotype change of the local cells, to osteoblast‐like or chondrocyte‐like cells that can deposit collagen and mediate the mineralization process according to a pathway resembling that described in Section 2.2.…”
Section: Pathological Calcificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathological calcifications have been linked to various health conditions such as renal and cardiovascular disorders, inflammation, and cancer. In particular, in breast and thyroid cancers, microcalcifications (MCs) have been linked to increased malignancy and poorer prognosis. , These MCs primarily comprise calcium phosphate (CaP) minerals, mainly carbonated hydroxyapatite (HA). In vitro studies have demonstrated that breast cancer cells exposed to HA crystals exhibit enhanced malignancy behavior, suggesting a potential connection between inhibiting crystallization and suppressing the progression of precancerous conditions. The crystallization of MCs typically occurs within the extracellular matrix (ECM), an environment in which the surrounding fluid, such as blood, is expected to be supersaturated with respect to HA. ,,, Under normal physiological conditions, certain mineralization inhibitors found in ECM fluids play a pivotal role in inhibiting MC formation. Developing a solution that mimics the properties of blood-like ECM fluid can provide a valuable platform for both investigating and controlling the crystallization of CaP in the tumor microenvironment. Simulated body fluids (SBFs) initially introduced by Kokubo et al have been extensively studied for biomimetic apatite formation and derived biomaterials. SBFs are designed to mimic the physiochemical properties of blood serum, include inorganic ions, and maintain a pH of 7.4 at 37 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Non-invasive imaging modalities in vivo include optical imaging, micro-computed tomography, magnetic resonance imaging (MRI), and positron emission tomography ( Appel et al, 2013 ; Nam et al, 2015 ; Eisenstein et al, 2016 ). In particular, MRI is highly suitable for monitoring tissue-engineered implants, owing to its safety without radiation exposure, excellent soft-tissue contrast, and high resolution without penetration depth restriction.…”
Section: Introductionmentioning
confidence: 99%